Bidirectional silicon‐controlled rectifier for advanced ESD protection applications. Issue 2 (1st January 2019) - Du, Feibo; Hou, Fei; Liu, Zhiwei; Liu, Jizhi; Liou, Juin J.
Abstract : In this Letter, an enhanced bidirectional modified lateral silicon‐controlled rectifier (EBMLSCR) is proposed for advanced dual‐directional electrostatic discharge (ESD) protection applications. The ESD characteristics of the novel EBMLSCR and conventional bidirectional modified lateral silicon‐controlled rectifier (BMLSCR) are measured using the transmission line pulsing tester. Compared with the BMLSCR, the EBMLSCR owns a lower trigger voltage down to 7.7 V, a higher failure current up to 6.5 A, a suitable holding voltage as well as the same superior leakage current. Based on these advantages, the proposed EBMLSCR can provide an effective ESD protection for the advanced 2.5 V/3.3 V input/output circuits, while the traditional BMLSCR becomes invalid for these applications due to its high trigger voltage and low robustness. In addition, the impact of some critical dimensions of the EBMLSCR has also been evaluated to further optimise the device performances.